An evaluation of the new tourist behavior model based on the extended theory of planned behavior - Trong Tien Bao Bui (Journal of Tourism, Heritage & Services Marketing, 2022)
Purpose: The current study aims to evaluate and validate travel intention through the extended theory of planned behaviour (TPB) and overall image of the destination, e-WOM, that travel intention linked to actual tourist behavior.